Development of employee payroll system in construction company using extreme programming method - Sihombing, Denny Jean Cross (SEAN Institute, 2024)
The management of employee payroll systems in construction companies is often faced with complex challenges, including the need for response speed, salary calculation accuracy, and user acceptance. A responsive and adaptive system can help operational efficiency and employee satisfaction. This research applies the Extreme Programming (XP) method in developing an employee payroll system, focusing on functionality testing, user evaluation, and stakeholder validation. The XP method was chosen because it can provide adaptive and responsive solutions to changing business needs. The user acceptance analysis and feature testing results showed the system's success, with the accuracy of salary calculation reaching 88 % and the user interface rated intuitive by users. Performance evaluation also showed an average system response speed of less than 2 seconds, indicating optimal responsiveness. Validation with stakeholders confirmed that the system met company policies and management expectations. The application of the XP method in developing an employee payroll system in a construction company positively impacted operational efficiency and user satisfaction. The conclusions of this study underline the successful implementation of the system and highlight the potential for further development to maintain the responsiveness and quality of the system over time.